A multimodal analysis of interpersonal meaning in Chinese as a second language classrooms / Heng Buai Chin - Heng, Buai Chin (2017)
This study explored the construction of interpersonal meanings through multimodal elements of teacher talk and teachers‘ body language in Chinese as a second language classrooms (CSL) in Malaysian primary schools. CSL classes have increasingly grown in numbers but has yet to gain the attention of researchers in examining their discourse. The study aims to: (1) identify the semiotic resources realised in CSL classrooms; (2) study the use of linguistic and non-linguistic semiotic resources to construct interpersonal meaning in CSL classrooms; and (3) study the impact of the interpersonal meaning constructed on the teaching and learning of CSL. An integrated theoretical framework which brings together various schools of thought namely Systemic-Functional Linguistics (SFL), teacher immediacy and multimodal discourse analysis, was adopted to examine the interpersonal meaning constructed in CSL classrooms, a first attempt in analyzing the discourse in Malaysia. In addition, educational theories were referred to in order to systematically discuss the deployment and co-deployment of various semiotic resources in constructing interpersonal meaning via teachers‘ roles and teacher-student relationships. The study proposes a comprehensive framework in analyzing teacher immediacy, a realisation of interpersonal meaning. Data were obtained from four CSL teachers from four schools in Selangor, Malaysia and 63 students who attended the Level 4 CSL course in the schools through classroom observations, recording of classroom lessons and interviews with the teachers and students. The study not only provides empirical data which is lacking in research previously carried out in Malaysia identifying resources use in the teaching of second language but also discusses the co-deployment of verbal and non-verbal resources evident in classroom discourse to create meaning. In addition, the study impresses upon the importance of time parameter and space to provide richer discussions of the semiotic resources identified. Other findings include the fact that CSL teachers were to some extent multilingual such that they can code-switch between Chinese, Malay and English, were sensitive to the cultural norms of the various races in the classes, used the lexical item ‗teacher‘ to refer to themselves in teacher talk, appraised students positively through the use of judgement resources and are creative in negotiating the various resources at every stage of their teaching, able to foreground and background resources wherever relevant. Strategies through the enactment of various teacher‘s roles were identified to realize teacher immediacy such as remembering students‘ names, code-switching to facilitate student‘s learning, smiling frequently, and establishing frequent eye contact. Such immediate behaviour of the teachers have positive impact on the teaching and learning of CSL which includes reducing learning anxiety, increasing motivation and interest in learning, developing student‘s confidence, instilling good behaviour and developing student‘s discipline. These in turn help establish a close rapport and a meaningful teacher-student relationship, creating a conducive learning environment for teaching and learning. The findings of this study will benefit teachers of not only CSL classes but teachers of other disciplines, developers of teaching programs as well as researchers in the field of multimodal discourse.